Toward a Rational Design of 3d-4f Heterometallic Coordination Polymers Based on Mixed Valence Copper Centers - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2019)
In the present work, we report two new CuI/CuII-GdIII mixed valence heterometallic coordination polymers (HCP), [Gd(H2O)4CuIICuI(IDC)2] (1) and [Gd2(H2O)2(C2O4)2CuII(IDC)2CuI 2(4,4′-bipy)]·4.5H2O (2) obtained under solvothermal synthesis using 1H-imidazole-4,5-dicarboxylic acid (H3IDC) as a principal N,O-bifunctional organic linker. In both compounds, the stabilization of the CuI cations is achieved only by the coordination of N-Atoms belonging to the organic ligands. While 1 presents a two-dimensional honeycomb network obtained by the coordination of single organic linker (IDC3-), 2 contains three different organic ligands (IDC3-, C2O4 2-, and 4,4′-bipy), which allow the construction of a three-dimensional network. From a magnetic point of view, 1 and 2 behave as simple paramagnets at high temperature, presenting ferromagnetic interactions below 50 K, and a positive magnetic coupling constant of J = 0.60 cm-1 and J = 0.22 cm-1 was obtained for 1 and 2 respectively. To the best our knowledge, 1 and 2 correspond to the second and third reported examples containing a CuI/CuII mixed valence system assembled with GdIII cations, thus enriching the chemistry involved in 3d-4f metal-organic materials. Copyright © 2019 American Chemical Society.